Amphibious shelter-builder Oniscidea species from the New World with description of a new subfamily, a new genus and a new species from Brazilian cave (Isopoda, Synocheta, Styloniscidae). - Leila A Souza; Rodrigo L Ferreira; André R Senna (PLoS ONE, 2015)
The new subfamily Iuiuniscinae, Styloniscidae, is erected for the new genus Iuiuniscus and the new species I. iuiuensis, which is described from cave of the State of Bahia, Northeastern Brazil. A special ecological character is shown here for the first time for a New World Oniscidea: the construction of mud shelters. An introduction addressing the systematics of Synocheta with emphasis on Styloniscidae Vandel, 1952 is provided, as well as general comments about the dependence of water in some Oniscidea and ecological traits of amphibious Synocheta. The problems referring to nomenclature, taxonomy and the interrelationships in Styloniscidae are discussed.